2013
DOI: 10.1002/lary.24047
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of antiallergic effects of pneumococcal conjugate vaccine and pneumococcal polysaccharide vaccine in a murine model of allergic rhinitis

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 22 publications
3
8
0
Order By: Relevance
“…The present study demonstrated that intranasal pretreatment with PC suppresses nasal symptoms and allergic inflammation of the nasal mucosa in a murine model of AR. The inhibitory effects of intranasal immunization with PC on nasal symptoms are similar to those reported by previous studies, in which nasal symptoms in a murine AR model induced by sensitization with Der f were reduced by intranasal pretreatment with pneumococcal polysaccharide vaccine and pneumococcal conjugate vaccine . Furthermore, in the present study, the levels of serum IgE and eosinophil infiltration into the nasal mucosa were significantly decreased by intranasal PC pretreatment similar to the experiments using pneumococcal vaccines .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The present study demonstrated that intranasal pretreatment with PC suppresses nasal symptoms and allergic inflammation of the nasal mucosa in a murine model of AR. The inhibitory effects of intranasal immunization with PC on nasal symptoms are similar to those reported by previous studies, in which nasal symptoms in a murine AR model induced by sensitization with Der f were reduced by intranasal pretreatment with pneumococcal polysaccharide vaccine and pneumococcal conjugate vaccine . Furthermore, in the present study, the levels of serum IgE and eosinophil infiltration into the nasal mucosa were significantly decreased by intranasal PC pretreatment similar to the experiments using pneumococcal vaccines .…”
Section: Discussionsupporting
confidence: 90%
“…The same results were observed in the experiments using pneumococcal vaccines, although the administration of killed Spn before OVA sensitization significantly enhanced IFN‐γ production from mediastinal lymph node T cells . Furthermore, it has been reported that regulatory T cells are associated with the suppression of Th2‐type immune response by pneumococcal vaccines . Although PC is a T cell‐independent antigen and does not induce regulatory T cells, conjugation to a protein carrier such as KLH allows the involvement of T cells, indicating that intranasal administration of PC‐KLH might have induced regulatory T cells and suppressed IL‐4 production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite recent advances in understanding the mechanisms underlying allergic inflammation, current therapies can only alleviate the symptoms of disease. [4] Since these therapies are still imperfect, it is important to continue to study the pharmacology of this disease as part of the search to obtain better drugs.…”
mentioning
confidence: 99%
“…Many important pharmacological agents have been used to treat AR (6). Pycnogenol ® (PYC) is a natural plant extract achieved from the French maritime pine Pinus pinaster bark (Pinus maritime) (7,8).…”
mentioning
confidence: 99%